In vitro biofilm formation of Gardnerella vaginalis and Escherichia coli associated with bacterial vaginosis and aerobic vaginitis - Shang, Xiang; Bai, Huihui; Fan, Linyuan; Zhang, Xin; Zhao, Xiaowen; Liu, Zhaohui (Frontiers in Cellular and Infection Microbiology, 2024)
Objective To determine the optimum biofilm formation ratio of Gardnerella vaginalis (G. vaginalis) in a mixed culture with Escherichia coli (E. coli). Methods G. vaginalis ATCC14018, E. coli ATCC25922, as well as five strains of G. vaginalis were selected from the vaginal sources of patients whose biofilm forming capacity was determined by the Crystal Violet method. The biofilm forming capacity of E. coli in anaerobic and non-anaerobic environments were compared using the identical assay. The Crystal Violet method was also used to determine the biofilm forming capacity of a co-culture of G. vaginalis and E. coli in different ratios. After Live/Dead staining, biofilm thickness was measured using confocal laser scanning microscopy, and biofilm morphology was observed by scanning electron microscopy. Results The biofilm forming capacity of E. coli under anaerobic environment was similar to that in a 5% CO2 environment. The biofilm forming capacity of G. vaginalis and E. coli was stronger at 106:105 CFU/mL than at other ratios (P<0.05). Their thicknesses were greater at 106:105 CFU/mL than at the other ratios, with the exception of 106:102 CFU/mL (P<0.05), under laser scanning microscopy. Scanning electron microscopy revealed increased biofilm formation at 106:105 CFU/mL and 106:102 CFU/mL, but no discernible E. coli was observed at 106:102 CFU/mL. Conclusion G. vaginalis and E. coli showed the greatest biofilm forming capacity at a concentration of 106:105 CFU/mL at 48 hours and could be used to simulate a mixed infection of bacterial vaginosis and aerobic vaginitis in vitro.